2003
DOI: 10.1111/1540-5893.3703002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Procedural Justice and Legitimacy in Shaping Public Support for Policing

Abstract: This study explores two issues about police legitimacy. The first issue is the relative importance of police legitimacy in shaping public support of the police and policing activities, compared to the importance of instrumental judgments about (1) the risk that people will be caught and sanctioned for wrongdoing, (2) the performance of the police in fighting crime, and/or (3) the fairness of the distribution of police services. Three aspects of public support for the police are examined: public compliance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

110
2,705
8
70

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 2,272 publications
(2,893 citation statements)
references
References 22 publications
110
2,705
8
70
Order By: Relevance
“…On the other hand, a strong and proactive police presence also has the potential to promote adolescent well-being, positive feelings about the police, and a sense of security among urban residents, through fair and just practices and improvements to public safety (Powell, 2012;Sunshine & Tyler, 2003;Tyler & Huo, 2002). While these benefits may accrue predominantly to those not personally stopped by the police, youth may also benefit from contact with the police, particularly if these interactions divert them from risky activities or encourage respectful relationship-building within their community (Skogan, Hartnett, Bump, & Dubois, 2008).…”
Section: Policing and Legal Socializationmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, a strong and proactive police presence also has the potential to promote adolescent well-being, positive feelings about the police, and a sense of security among urban residents, through fair and just practices and improvements to public safety (Powell, 2012;Sunshine & Tyler, 2003;Tyler & Huo, 2002). While these benefits may accrue predominantly to those not personally stopped by the police, youth may also benefit from contact with the police, particularly if these interactions divert them from risky activities or encourage respectful relationship-building within their community (Skogan, Hartnett, Bump, & Dubois, 2008).…”
Section: Policing and Legal Socializationmentioning
confidence: 99%
“…More recently research has suggested that legitimacy also influences the willingness to cooperate with legal authorities, including police officers and judges (Sunshine & Tyler, 2003;Tyler & Fagan, 2008). Hence, it was anticipated that legitimacy would influence law related behavior, a hypothesis we test below.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…For example the British Crime Survey shows a steady decrease in the proportion of respondents who judge their local police to be doing a very good or fairly good job, dropping from 90% in 1982 to 75% in the financial year 2002/2003(Nicholas & Walker, 2004. Public support and cooperation may suffer as a result (Tyler & Huo, 2002;Sunshine & Tyler, 2003b). Reiner (1992Reiner ( , 2000 provides the most influential thesis on the historical trajectory of police legitimacy in Britain.…”
Section: Public Confidence In Policingmentioning
confidence: 99%